2020
DOI: 10.23960/jbm.v16i3.143
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Job Insecurity Terhadap Stres Kerja, Kinerja dan Turnover Intention Karyawan

Abstract: Contracting and outsourcing systems in a company certainly have a significant impact on the employment relationship between employees and companies. For employees, uncertainty can cause employees to be reluctant to make changes. With this, the intensity of the emergence of job insecurity is getting higher. The future of employees in the organization is increasingly uncertain and questionable. Job insecurity in the company will automatically affect the psychological condition of the workers and can cause stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
7
0
11
Order By: Relevance
“…The coefficient of determination test results show that job insecurity and workload contribute to work stress by 76.0%, while the remaining 24.0% is influenced by other variables not considered in this study. These findings align with previous research conducted by Bashori (2017), Saputri et al (2020), andMedysar (2019), which found that job insecurity has a positive and significant impact on employee work stress.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The coefficient of determination test results show that job insecurity and workload contribute to work stress by 76.0%, while the remaining 24.0% is influenced by other variables not considered in this study. These findings align with previous research conducted by Bashori (2017), Saputri et al (2020), andMedysar (2019), which found that job insecurity has a positive and significant impact on employee work stress.…”
Section: Resultssupporting
confidence: 92%
“…Research bySaputri et al (2020) indicates a positive and significant relationship between job insecurity and work-related stress because high levels of job insecurity among employees can influence the occurrence of work-related stress. However, a study byRikardo and Susanti (2020) yielded different results, suggesting that job insecurity does not have a direct impact on work-related stress.Workload also plays a significant role in work-related stress.…”
mentioning
confidence: 99%
“…Job Insecurity merujuk pada pendapat yang di kemukan (Al Amin & Pancasasti, 2021) merupakan suatu keadaan yang tidak pasti tentang pekerjaan yang berkelanjutan. Ketidakamanan kerja tidak hanya berkaitan dengan hilangnya potensi lapangan kerja tetapi juga dengan ketidakpastian mengenai isu-isu pekerjaan dan karir termasuk tingkat tanggung jawab seseorang dan kesempatan promosi (Saputri et al, 2020).Indikator Job Insecurity merujuk pada (Al Amin & Pancasasti, 2021) :…”
Section: Job Insecurityunclassified
“…Tingginya angka turnover intention tersebut juga merupakan faktor penghambat bagi perusahaan untuk mencapai tujuannya. Sebagaimana didukung oleh teori motivasi Herzberg (Septiari & Ardana, 2016) dimana teori ini membagi situasi yang memengaruhi sikap seseorang terhadap pekerjaannya.…”
Section: Pendahuluanunclassified
“…Terjadinya turnover intention merupakan suatu hal yang tidak diinginkan perusahaan, sebab dapat mengakibatkan kerugian baik dilihat dari segi biaya, waktu, maupun sumber daya yang digunakan. Minanti et al, (Safitri, 2019) menyatakan bahwa turnover intention dipengaruhi oleh beberapa faktor, yaitu job insecurity dan stres kerja, sementara menurut Menurut Irvianti dan Verina (Riani & Putra, 2017) turnover intention dipengaruhi oleh salah satu faktor yaitu beban kerja. Akan tetapi dalam penelitian ini hanya mengangkat dua faktor yang mempengaruhi turnover intention yaitu job insecurity dan beban kerja.…”
Section: Pendahuluanunclassified